Marked plaque regression in homozygous familial hypercholesterolemia. (June 2021) - Reeskamp, Laurens F.; Nurmohamed, Nick S.; Bom, Michiel J.; Planken, R. Nils; Driessen, Roel S.; van Diemen, Pepijn A.; Luirink, Ilse K.; Groothoff, Jaap W.; Kuipers, Irene M.; Knaapen, Paul; Stroes, Erik S.G.; Wiegman, Albert; et al.
Abstract: Background and aims: Both plasma low-density lipoprotein (LDL) cholesterol levels and risk for premature cardiovascular disease are extremely elevated in patients with homozygous familial hypercholesterolemia (HoFH), despite the use of multiple cholesterol lowering treatments. Given its inborn nature, atherosclerotic plaques are commonly observed in young HoFH patients. Whether intensive lipid lowering strategies result in plaque regression in adolescent patients is unknown. Methods: Two HoFH patients with null/null LDLR variants, who participated in the R1500-CL-1629 randomized clinical trial (NCT03399786) evaluating the LDL cholesterol lowering effect of evinacumab (a human antibody directed against ANGPTL3; 15 mg/kg intravenously once monthly), were included in this study. Patients underwent coronary computed tomography angiography (CCTA) before randomization and after 6 months of treatment. Results: Both patient A (aged 12) and B (aged 16) were treated with a statin, ezetimibe and weekly apheresis. Evinacumab decreased mean pre-apheresis LDL cholesterol levels from 5.51 ± 0.75 and 5.07 ± 1.45 mmol/l to 2.48 ± 0.31 and 2.20 ± 0.13 mmol/l and post-apheresis LDL levels from 1.45 ± 0.26 and 1.37 ± 39 mmol/l to 0.80 ± 0.16 and 0.78 ± 0.13 mmol/l in patient A and B, respectively. Total plaque volumes were reduced by 76% and 85% after 6 months of evinacumab treatment in patient A and B, respectively. Conclusions: We describe two severely affected young HoFH patients in whom profound plaque reduction was observed with CCTA after intensive lipid lowering therapy with statins, ezetimibe, LDL apheresis, and evinacumab. This shows that atherosclerotic plaques possess the ability to regress at young age, even in HoFH patients. Graphical abstract: Image 1 Highlights: Homozygous familial hypercholesterolemia (HoFH) is characterized by the presence of coronary plaques at a young age. Two adolescent HoFH patients with profound plaques received aggressive low-density lipoprotein (LDL) lowering. Profound coronary plaque regression was observed on CCTA imaging. Atherosclerotic plaques possess the ability to regress at young age, even in HoFH.